Implementing Role Play to Teach Speaking Skills for Secretarial Purposes: A Diploma III Case Study - Fitria Wahyu Nugraheni; Marius Pramana (International Journal of Educational Development, 2025)
This study explores the effectiveness of role play as a teaching method to enhance students' speaking skills in professional secretarial contexts, specifically in business telephone conversations, presentations, and negotiations. The research was conducted within the Diploma III Secretarial Program over one academic semester. Employing a qualitative methodology, the study involved classroom observations and student reflections gathered through feedback sessions. The objective was to assess how role play could contribute to the development of fluency, confidence, and contextual language use in English for specific professional purposes. The findings revealed that role play significantly improved students' speaking performance. Students showed greater confidence in expressing ideas, improved fluency, and a better understanding of appropriate vocabulary and expressions suited to professional environments. Furthermore, students expressed that the interactive and practical nature of role play made learning more enjoyable and less intimidating, allowing them to immerse themselves in real-life communication scenarios. These positive experiences encouraged active participation and increased motivation to learn English for professional use. The study also highlighted the value of reflective learning, as students were able to identify their own progress and areas for improvement. Through continuous engagement in simulated professional tasks, learners developed better adaptability in communication and exhibited more natural conversational flow during tasks that mirrored real workplace situations. In conclusion, the role play method proves to be a highly effective pedagogical tool for enhancing speaking skills in secretarial English. It not only helps build linguistic competence but also cultivates soft skills necessary for professional communication. Therefore, it is recommended that educators incorporate role play regularly in English for Specific Purposes (ESP) curricula to maximize its benefits in developing productive speaking abilities among students.